Internalizing Lego-lego of Buginese People into Project Based Learning Model - Nasruddin, Nasruddin; Jumaisa, Jumaisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to reveal the concept of lego-lego in the project-based learning model. This study is a literature that uses a conceptual approach and focuses on the combination of the Project Based Learning model with intrinsic values in society, especially in South Sulawesi. Types and sources of data are obtained from primary data in the form of documents related to learning models based on Project Based Learning. Lego-lego can provide learning values so as to redevelop various skills and visual intelligence, creativity, and character of learners in completing their tasks